1998
DOI: 10.1191/095968398667891349
|View full text |Cite
|
Sign up to set email alerts
|

Pollen and mollusc records for environmental change in central Spain during the mid- and late Holocene

Abstract: The central part of the Iberian Peninsula has few radiocarbon dated records of vegetation and climatic history for the Holocene. Extinct and active tufa-forming sites occur along the northwestern margin of the Sierra de Alcaraz. Tufas are often closely associated with the remains of plants and animals, and two extinct systems near the settlements of El Jardin and Alcaraz have yielded a record of environmental history that spans much of the last 6000 years. The record indicates that the present-day sedimentolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 20 publications
2
38
0
1
Order By: Relevance
“…recorded in the Guadalaviar river in the Iberian Range (Sancho et al, 1997). Furthermore, Taylor et al (1998) record significant Holocene tufa development from about 6.0 ka B.P. to 3.0 ka B.P.…”
Section: Discussionmentioning
confidence: 98%
“…recorded in the Guadalaviar river in the Iberian Range (Sancho et al, 1997). Furthermore, Taylor et al (1998) record significant Holocene tufa development from about 6.0 ka B.P. to 3.0 ka B.P.…”
Section: Discussionmentioning
confidence: 98%
“…Similar studies have demonstrated that errors for the last interglacial comprise several thousand years and that vertical evolution of tufa deposits commonly falls within the error of measurements (Frank et al, 2000). Additionally, taking into consideration the growth rate of tufa deposits in the region (Taylor et al, 1998;Ordoñez et al, 2005), and the maximum thickness of the tufa deposits (i.e.,~10 m) dates from different depths should fall within the analytical error. Therefore, the sampling strategy of the tufa deposit for age determination was conducted in order to obtain at least a precise date for a specific level in the section rather than trying to obtain top and bottom ages.…”
Section: Methodsmentioning
confidence: 88%
“…in Iberia (Schulte, 2002;Taylor et al, 1998), the Alpine chain (Steinmann, 1978;Veit, 1993), Italy (Biagi et al, 1993;Cremaschi, 1987), northern Africa (Zielhofer et al, 2002(Zielhofer et al, , 2004, and Eastern Europe (Alexandrovskiy and Chichagova, 1998)dand is assumed to be the most intense among Holocene pedogenetic phases. Mid-Holocene pedogenesis has usually been related to the climate optimum (also known as hypsithermal, Holocene thermal optimum, etc.de.g.…”
Section: Discussionmentioning
confidence: 99%